Hubungan tingkat pengetahuan dengan kebiasaan menyikat gigi pada anak kelas III-V di SDN 8 Langkai Palangka Raya - Savindra, Andine Putri; Lestarisa, Trilianty; Jelita, Helena; Kahanjak, Donna Novina; Surbakti, Ranintha Br (Fakultas Kedokteran Universitas Palangka Raya, 2024)
Oral and dental health care is a unity that affects the health condition of the body which cannot be separated. At an early age it is necessary to maintain oral health. Nowadays, many children do not know the importance of paying attention to brushing teeth habit in a proper ways so that problems are often found, one of which is cavities. Maintenance of good dental health must be supported by good knowledge. This study aims to determine the relationship between the level of knowledge and the habit of brushing teeth in class III-V children at SDN 8 Langkai Palangka Raya. This study used an analytic observational approach with a cross sectional method, which was a type of research that was carried out one time with the Spearman statistical test, significance p < 0.05. The results of the study found that 92 (93.9%) respondents were found to have a good level of knowledge, with 52 (53.1%) respondents with moderate tooth brushing habits. The results of bivariate analysis showed that there was a relationship between the level of knowledge and the habit of brushing teeth in children in grades III-V at SDN 8 Langkai Palangka Raya with the results of the Spearman statistical test p value = 0, 003 (<0.05). There is a relationship between the level of knowledge and the habit of brushing teeth in grade III-V at SDN 8 Langkai Palangka Raya.